2006
DOI: 10.2165/00002512-200623010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospitalisation in an Acute Medical Geriatric Unit on Potentially Inappropriate Medication Use

Abstract: Hospitalisation in geriatric services results in a reduction in potentially inappropriate medication use. Improved pharmacological education of practitioners, especially with regard to drug adverse effects, is desirable to improve management of geriatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 28 publications
4
83
1
6
Order By: Relevance
“…The prevalence of PIM use also decreased, from 66% (95% CI 63.8-68.0) on admission to 44% (95% CI 41.3-45.9) at discharge. 1 Although the current study concurred with these results in terms of a statistically significant reduction in PIMs, this change may not be considered clinically significant. The proportion of patients with an overall change in PIMs during the hospital stay may be more clinically relevant.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The prevalence of PIM use also decreased, from 66% (95% CI 63.8-68.0) on admission to 44% (95% CI 41.3-45.9) at discharge. 1 Although the current study concurred with these results in terms of a statistically significant reduction in PIMs, this change may not be considered clinically significant. The proportion of patients with an overall change in PIMs during the hospital stay may be more clinically relevant.…”
Section: Discussionsupporting
confidence: 77%
“…12 We believe that admission to hospital provides an opportunity to make changes in the type of drugs and the total number of PIMs prescribed. 1 The goal of this study was to determine the influence of hospital admission on the use of medications known to increase the risk of falls in older adults (as defined by the 2012 Beers criteria) among patients admitted to the authors' tertiary care facility after experiencing a fall. The primary objective was to determine the proportion of patients over the age of 65 years who were admitted to hospital with a diagnosis of falls and at least one PIM identified on a best possible medication history (BPMH) at the time of admission who had a change in the total number or dosage of PIMs upon discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Vonbach et al (2008), 47% of all pDDI at hospital discharge were the result of medication changes during hospitalization. However, Laroche et al (2006) demonstrated that the prescription of anticholinergic and inappropriate drugs among geriatric inpatients decreased at discharge, showing that hospitalization could provide an opportunity to reassess pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Curiosamente, já houve observação documentada de que a hospitalização de pacientes geriátricos pode resultar em atenuação na prescrição de MPIs, constituindo uma oportunidade de rever o tratamento farmacológico (LAROCHE et al, 2006). PRMs, além de representarem um sério risco à saúde do paciente, também estão diretamente associados ao aumento de custos nos serviços de saúde.…”
Section: Existem Duas Definições De Prm Dignas De Nota De Acordo Comunclassified